A PSYCHOLINGUISTIC ANALYSIS OF THE "TIP OF THE TONGUE" (TOT) PHENOMENON AMONG BILINGUAL STUDENTS DURING ORAL PRESENTATIONS - Muhammad Zikran Ishak; Wiyanda Jaya Ismail; Maulida Ulfa Fadila Bisango; Aulia Mundok; Muziatun Mukadji (Jurnal Review Pendidikan dan Pengajaran, 2026)
The Tip of the Tongue (TOT) phenomenon is a condition when someone temporarily cannot recall a word even though they already know it. This phenomenon often occurs in bilingual speakers because two language systems are active at the same time, which can cause difficulties in lexical retrieval during speaking activities. In academic settings, especially oral presentations, students may experience TOT because of nervousness, language interference, and pressure while speaking spontaneously.This study aims to investigate the occurrence of the Tip of the Tongue phenomenon among bilingual students during oral presentations and to identify the strategies they use to overcome lexical retrieval difficulties. The study uses a descriptive qualitative method. The data were collected through observation and recording students’ oral presentations.The findings show that TOT frequently appears when students experience high cognitive load and speaking anxiety. To deal with these difficulties, students commonly use strategies such as phonological cues, semantic associations, and code-switching. These findings indicate that bilingual lexical processing plays an important role in students’ speaking performance. This study is expected to provide useful insights for improving students’ fluency and confidence in academic speaking contexts.